Generation of Reactive Oxygen Species in the Reaction Catalyzed by α-Ketoglutarate Dehydrogenase - Tretter, Laszlo (J Neurosci, 2004)
α-Ketoglutarate dehydrogenase (α-KGDH), a key enzyme in the Krebs' cycle, is a crucial early target of oxidative stress (Tretter and Adam-Vizi, 2000). The present study demonstrates that α-KGDH is able to generate H(2)O(2) and, thus, could also be a source of reactive oxygen species (ROS) in mitochondria. Isolated α-KGDH with coenzyme A (HS-CoA) and thiamine pyrophosphate started to produce H(2)O(2) after addition of α-ketoglutarate in the absence of nicotinamide adenine dinucleotide-oxidized (NAD(+)). NAD(+), which proved to be a powerful inhibitor of α-KGDH-mediated H(2)O(2) formation, switched the H(2)O(2) forming mode of the enzyme to the catalytic [nicotinamide adenine dinucleotide-reduced (NADH) forming] mode. In contrast, NADH stimulated H(2)O(2) formation by α-KGDH, and for this, neither α-ketoglutarate nor HS-CoA were required. When all of the substrates and cofactors of the enzyme were present, the NADH/NAD(+) ratio determined the rate of H(2)O(2) production. The higher the NADH/NAD(+) ratio the higher the rate of H(2)O(2) production. H(2)O(2) production as well as the catalytic function of the enzyme was activated by Ca(2+). In synaptosomes, using α-ketoglutarate as respiratory substrate, the rate of H(2)O(2) production increased by 2.5-fold, and aconitase activity decreased, indicating that α-KGDH can generate H(2)O(2) in in situ mitochondria. Given the NADH/NAD(+) ratio as a key regulator of H(2)O(2) production by α-KGDH, it is suggested that production of ROS could be significant not only in the respiratory chain but also in the Krebs' cycle when oxidation of NADH is impaired. Thus α-KGDH is not only a target of ROS but could significantly contribute to generation of oxidative stress in the mitochondria.